Guardians of the hallways? School resource officers and bullying. Issue 4 (1st October 2018) - Broll, Ryan; Lafferty, Robin
Abstract : Purpose: School resource officers (SROs) have become commonplace in schools across the USA. Although their visibility may allow them to function as capable guardians, little research has examined their impact on less serious but more common forms of school violence, like bullying. The purpose of this paper is to examine the relationship between the presence, quantity and roles of SROs and the frequency of bullying. Design/methodology/approach: Data come from the nationally representative 2006 School Survey on Crime and Safety. The relationship between SROs and bullying, controlling for other guardians, motivated offenders and school characteristics, was assessed using ordered logistic regression. Separate models were estimated for middle and high schools. Findings: There was no association between the presence, quantity or role of SROs and bullying in middle or high schools; however, teacher training was associated with less frequent bullying, especially in middle schools, and the presence of motivated offenders was associated with more frequent bullying. Research limitations/implications: Whether SROs reduce school violence is contested; this study found no association between SROs and bullying, a less serious but more common form of school violence. Future research should consider the roles of SROs in schools and the credibility of capable guardians. Practical implications: The results caution against continuing to divert educational and social service resources to law enforcement in schools. Continued training for teachers may provide more effective guardianship against bullying. Originality/value: This paper contributes to the developing literature on the effect of SROs on less serious but more common forms of school violence, like bullying.